Community Aging in Place, Advancing Better Living for Elders (CAPABLE) program: Understanding the potential involvement of care partners. (6th August 2021) - Fields, Beth; Yanes, Caylee; Ennis, Molly; Toto, Pamela
Abstract: Older adults frequently turn to care partners for support to remain in their homes for as long as possible. Yet, many evidence‐based home and community programs to support ageing in place do not formally involve care partners. This study sought to understand how to involve care partners in the Community Aging in Place, Advancing Better Living for Elders (CAPABLE) program. A qualitative descriptive study was conducted. Framework analysis of multiple sources of data, including descriptions from stakeholders ( N  = 24) and available CAPABLE resources, provided the basis for understanding how to involve care partners in the program. Considerations for involving care partners when initiating, delivering and following the program were generated; namely, providing older adults' choices while screening for the program, defining roles and sharing information in a collaborative manner and reinforcing knowledge and skills training. Embracing these considerations in geriatric practice and research efforts is likely to help care partners' ability to provide assistance, thus enabling older adults to remain in their homes for as long as possible. Providers can use findings to better involve and support care partners in their delivery of programs to older adults. Researchers should further develop and test a care partner‐supported CAPABLE program.